Caffeate and piperidine-3-ol derivatives from the stem bark of Cassia sieberiana. Issue 15 (3rd August 2021) - Atontsa, Brice Cedric K.; Bitchagno, Gabin Thierry M.; Mpetga, James D. Simo; Wamba, Brice Elvis N.; Nayim, Paul; Tchuenguem, Roland T.; Ndontsa, Blanche L.; Koagne, Romeol R.; Opatz, Till; Kuete, Victor; Tane, Pierre
Abstract: A new caffeate derivative from the ethanol extract of the stem bark of Cassia sieberiana DC. is described herein along with the known secondary metabolites spectaline (2 ), iso -6-cassine (3 ), 3- O -methyl- chiro -inositol (4 ), monobehenin (5 ), octyl nonadecyloate (6 ), β -sitosterol (7 ), stigmasterol (8 ) and sitosterol 3- O - β -D-glucopyranoside (9 ). The chemical structures were elucidated by means of various spectroscopic and spectrometric techniques. Extract and isolated compounds were devoid of inhibitory action against the herein selected bacterial strains (MICs > 256 μg/mL) but showed capacities to reduce 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical (EC50  < 3 μg/mL) considerably better than the "gold standard" trolox (EC50 6.47 ± 0.48 μg/mL). Graphical Abstract: